ANALYSIS OF STUDENT OPINIONS AND OPTIMIZATION OF MARKETING STRATEGY BASED ON BIG DATA TECHNOLOGIES IN THE PROCESS OF DIGITALIZATION OF HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
The study analyzes studentsʼ opinions during the digital transformation of higher education institutions using Big Data technologies. Data were collected from online platforms, social networks, and surveys. Sentiment analysis, topic modeling, and SWOT anal ysis were applied to identify key challenges and opportunities. The findings provide a basis for improving digital services, enhancing student satisfaction, and optimizing marketing strategies for universities.
Keywords: digital transformation; Big Data; sentiment analysis; topic modeling; SWOT analysis; higher education